2017
DOI: 10.1007/s13142-017-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a statewide dissemination and implementation of physical activity intervention in afterschool programs: a nonrandomized trial

Abstract: In 2015, YMCA-operated afterschool programs (ASPs) across South Carolina pledged to achieve the national standard that calls for every child to accumulate 30 min/day of moderate-to-vigorous physical activity (MVPA) during program time. This study shares the first-year findings related to the dissemination, implementation, and outcomes associated with the statewide intervention to achieve the MVPA Standard. Twenty ASPs were sampled from all YMCA-operated ASPs (N = 97) and visited at baseline (spring 2015) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Our findings highlight that intervention researchers need to carefully consider whether information obtained from pilot tests of an intervention delivered by highly trained research team members, with extensive support for intervention delivery, over short timeframes with different measures than are to be used in the larger-trial can be sustained and is consistent with what is intended to-be-delivered in the efficacy/effectiveness trial. Including one or more of these biases in a pilot study could result in inflated estimates of effectiveness during the pilot and lead interventionists to believe the intervention is more effective than the actual effect achieved when delivered in a efficacy/effectiveness trial without these biases [14,26,166]. These are critical decisions because, if the purpose of a pilot study is to determine whether a large-scale trial is warranted, yet the outcomes observed from the pilot study are contingent upon the features included in the pilot that are not intended to be or cannot be carried forward in an efficacy/effectiveness trial, the likelihood of observing limited or null results in the efficacy/effectiveness trial is high.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight that intervention researchers need to carefully consider whether information obtained from pilot tests of an intervention delivered by highly trained research team members, with extensive support for intervention delivery, over short timeframes with different measures than are to be used in the larger-trial can be sustained and is consistent with what is intended to-be-delivered in the efficacy/effectiveness trial. Including one or more of these biases in a pilot study could result in inflated estimates of effectiveness during the pilot and lead interventionists to believe the intervention is more effective than the actual effect achieved when delivered in a efficacy/effectiveness trial without these biases [14,26,166]. These are critical decisions because, if the purpose of a pilot study is to determine whether a large-scale trial is warranted, yet the outcomes observed from the pilot study are contingent upon the features included in the pilot that are not intended to be or cannot be carried forward in an efficacy/effectiveness trial, the likelihood of observing limited or null results in the efficacy/effectiveness trial is high.…”
Section: Discussionmentioning
confidence: 99%
“…Reassignment of staff, changes in staff workloads, and changes in leadership led to discontinuation of an evidence-based trauma intervention in a large urban school district [48]. Lack of organizational policy to support staff time to attend training led to partial implementation of after school physical activity efforts [49]. But in the present study, ending of funding was by far the most commonly reported reason for inappropriate termination, as found in a recent review [50], and organizational supports were not protective.…”
Section: Discussionmentioning
confidence: 99%
“…Public health systems are working to scale up EBIs [22,45,49], but little is known about strategies to address inappropriate continuation of ineffective approaches. Here public health can learn from medical studies, even though organizational structures and funding sources differ.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated PA and SB in the school context, especially considering full-day school's ASPs: Beets et al ( 17 ) showed in their study with more than 1,000 elementary school children attending 97 ASPs in South Carolina, USA, operated by the Young Men's Christian Association (YMCA), that only one quarter reached the 30-min guideline of PA in ASPs. On average, children spent 21.4 min in MVPA and 64.3 min in SB at baseline.…”
Section: Introductionmentioning
confidence: 99%